THE USAGE OF E-HRM AND HRM EFFECTIVENESS: EMPIRICAL EVIDENCE FROM THE INDONESIAN BANKING SECTOR - Pangeran; Ismayani (RADJA PUBLIKA, 2023)
e-HRM is an information technology that can increase the effectiveness and efficiency of a company's HRM system by carrying out the system's functions electronically or online. This study aims to analyze the effect of the use of electronic human resource management (e-HRM) on the effectiveness of HRM in banking companies. The Unified Theory of Acceptance and Use of Technology (UTAUT) is used as a theory to analyze the influence of e-HRM determinants (performance expectancy, effort expectancy, and social influence) on the use of e-HRM systems. Empirical data were obtained through questionnaires distributed to one of the banking companies in Indonesia. Hypothesis analysis was performed using the Structural Equation Modeling (SEM) technique using Lisrel 8.80 software. These findings indicate that performance expectancy and effort expectancy can affect employees' use of the e-HRM system. The use of the e-HRM system has also been shown to have a positive and significant influence on the effectiveness of HRM at the policy and practice levels.